Calculation of the isomorfic mixture limit in the system Ln3[M]2M3O12 - Ln3[Sc]2M3O12 (Ln = La-Lu,Y; M = Ga, Al) - G. M. Kuz’micheva; A. A. Sattarova (Тонкие химические технологии, 2009)
The method of solid solution calculation in the system Ln3[М2]M3O12 - Ln3[ScyМ2-y]M3O12 (Ln = La-Lu, Y; М = Ga, Al) has been developed. The theoretical model has been confirmed by experimental data.